(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Anyone under the age of 18 is referred to as a Juvenile or Child. Any individual under theage of 18 is considered a Child under international law. This definition of a kid comes from the UnitedNations Convention on the Rights of the kid (UNCRC), which is now universally recognized. Any personunder the age of eighteen is considered a juvenile or Child under Section 2(k) of the Juvenile JusticeCare and Protection of Children Act, 2000. The children of a nation are its future. Therefore, everyone hasa duty and obligation to make sure that the children live in a safe environment. However, like a sicknessin our society, juvenile criminality has been found to drastically decline in a growing nation like India. Byconcentrating on the rules of the Juvenile Justice Act, 1986, 2000, 2014, and 2015, this research attemptsto explain the development of juvenile justice legislation from British India to the current democraticIndia. Although there is a safety regulation for these kids, the number of juvenile offenders is increasingnationwide, which is a major problem for the nation. Regardless of who is involved or the circumstances,justice delayed is justice denied. India, a country with great diversity, struggles with too many aspects ofjustice, from the social to the judicial levels. There are too many difficulties with juvenile justice in India,according to a variety of topics, but the study also seeks to identify the kinds and causes of juvenilecrimes in our society. In closing, some recommendations for preventing juvenile crimes have beenoffered by elucidating the development of juvenile justice in India.